Adult xanthogranulomatous disease of the orbit: case report of spontaneous regression and review of treatment modalities. (2nd January 2020) - Maeng, Michelle M.; Godfrey, Kyle J.; Jalaj, Sanjai; Kazim, Michael
ABSTRACT: Adult xanthogranulomatous disease of the orbit is a rare and incompletely understood entity. It can be limited to the orbit or be associated with systemic disease. While routine systemic surveillance is the standard of care for patients with orbital xanthogranulomatous disease, there is no universally accepted protocol for managing periorbital and orbital involvement. The authors report a case of adult orbital xanthogranuloma, without systemic disease, who, after 10 years of observation, demonstrated sustained radiographic regression of the lesions. To the authors' knowledge, this represents one of the first reports of spontaneous regression of untreated orbital xanthogranuloma, and supports observation of lesions that do not compromise ocular function. We present our case in the context of a major review of various treatment strategies described in the literature, including surgical resection, radiotherapy, plasmapheresis, corticosteroids, multiple immunomodulatory medications.